English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Prove by induction that the nth triangular number, T (sub n), is given by T (sub n)= (n/2)(n+1).

2007-05-23 18:22:35 · 4 answers · asked by Anonymous in Science & Mathematics Mathematics

4 answers

The keys to induction are to show that the relationship works for the smallest integer to which it applies, then to show that if it applies for one integer, it works for the next higher one. You can then show by repeated application that the relationship works for all integers greater than or equal to the one you started with.

For this example, the first step is to show that the relationship works for n = 1. That is easy. T (sub 1) = (1/2) (1 + 1) = (1/2)(2) = 1, which is indeed the first triangular number.

For the next step, we assume that the relationship works for some value n. Because a triangular number is the sum of all integers from 1 to n, the next higher triangular number above T(sub n) plus n + 1. Substituting our expression for T(sub n), we get

T (sub n+1) = (n/2)(n+1) + n + 1
= (n/2)(n+1) + 1(n+1)
= (n/2 + 1)(n+1)
= (n/2 + 2/2)(n+1)
= (n+2) * (1/2) * (n+1)
= (n+1) * (1/2) * (n+2)
= ((n+1)/2)(n+2)
= ((n+1)/2)((n+1)+1)
which is the expected value of T (sub n+1)

By induction, since the expression for T(sub 1) holds, so does that for T(sub 2)
and because T(sub 2) holds, so does T(sub 3)
and because T(sub 3) holds, so does T(sub 4)
and so on, for any arbitrarily large integer n.

2007-05-23 19:10:42 · answer #1 · answered by devilsadvocate1728 6 · 0 0

Base case for n=1, T(1) = 1

Now assume true for k

then

T(k+1) = T(k) + (k+1)
=(k/2)*(k+1) +(k+1)
=[(k/2)+1](k+1)
= [(k+2)/2](k+1)
={(k+1)/2](k+2)

Letting k+1 = n then you've shown that
T(n) = (n/2)(n+1)

which is what you wanted to show.

2007-05-23 18:54:53 · answer #2 · answered by modulo_function 7 · 0 0

if n =1 T(1) = 1
if n=2 , T(2) = 2+1 = 3 = (2/2)(2+1)

Say it is correct for n

prove for n+1, T(n+1) = T(n)+(n+1) = (n/2)(n+1) + (n+1) =

(n+1)(n+2)/2 = T(n+2), QED.

2007-05-23 18:56:53 · answer #3 · answered by TV guy 7 · 0 0

T(1) = 1
(1/2)(1+1)=1

T(2) = 1+2 = 3
(2/2)(2+1) = 3

Let it be true for n=m
T(m)=(m/2)((m+1)
Add m+1

(m/2)(m+1) + (m+1)
=(m+1)(m/2+1)
=[(m+1)/2](m+2)

Which is the format for T(m+1)

If it is true for n=1, it must be true for n=2
If it is true for n=2, it must be true for n=3
.
.

It ha been shown to be true for n=1
Therefore it is true for all values

2007-05-23 18:57:23 · answer #4 · answered by gudspeling 7 · 0 0

fedest.com, questions and answers